A solar cell and a method for preparing the same, and a method for improving the light absorption and transmission characteristics of a tin-based perovskite layer
By using a light-absorbing film with a heterojunction structure of a small molecule acceptor and a tin-based perovskite solar cell to blend the preparation of a heterojunction structure, the problems of low open circuit voltage and insufficient light response in the near-infrared region of tin-based perovskite solar cells are solved, and the photoelectric conversion efficiency is significantly improved.
Patent Information
- Application Number
- CN202111139117.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-09-28
AI Technical Summary
The open circuit voltage of tin-based perovskite solar cells is low, resulting in insufficient light response in the near-infrared region, limiting their performance improvement.
A light-absorbing layer film with a heterojunction structure of small molecule acceptor and tin-based perovskite is used to blend the light absorbing layer into a body to improve the light response of the perovskite absorbing layer to the long-wave direction, and to promote electron migration through appropriate energy level design and inhibit non-radiative recombination of carriers.
The photoelectric conversion efficiency of tin-based perovskite solar cells is significantly improved, and the open circuit voltage is increased by more than 20%, meeting the needs of commercial use.
Smart Images

Figure CN113937221B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic / inorganic composite solar cells, and in particular relates to a solar cell and a preparation method thereof, and a method for improving the light absorption and transmission characteristics of a tin-based perovskite layer. Background Art
[0002] At present, with the rapid growth of world energy demand, increasingly serious supply and demand and environmental problems have become the bottleneck restricting social and economic development. In particular, the intensified carbon emissions in recent years have led to extreme weather around the world. Therefore, it is urgent to establish a clean, sufficient, economical, safe and sustainable energy system. As global fossil energy is increasingly depleted and environmental pollution is getting worse, solar energy has gradually come into the public eye due to its inexhaustible, clean and pollution-free advantages, becoming one of the new energy sources with the greatest development potential. Among the many applications of solar energy, solar cells directly convert solar energy into electrical energy, which is one of the best ways to effectively utilize solar energy.
[0003] Metal halide perovskite solar cells have attracted widespread attention due to their low cost, simple preparation process and superior photovoltaic performance. So far, the certified photoelectric conversion efficiency has reached 25.2%, which is comparable to commercial silicon solar cells. Typical high-performance perovskite solar cells use lead-based perovskites as light absorption layers, but due to the strong toxicity of lead, the devices formed by them may cause serious harm to human health and the ecological environment. In addition, the optical band gap of lead-based perovskites is still not near the optimal Shockley-Queisser limit bandwidth of 1.34eV. In order to solve the above problems, scientists have tried to use a variety of metal ions to replace lead, but after experiments, only germanium and tin of the same family have the performance of replacing lead. Among them, tin has the closest characteristics to lead, with similar ionic radius and electronic configuration, and may also obtain more superior semiconductor properties. More importantly, tin is a low-toxic element, and divalent tin ions will degrade into eco-friendly tin dioxide when exposed to air, which is almost harmless to the environment.
[0004] Although tin-based perovskites have similar electronic structures and comparable semiconductor properties to lead-based perovskites, including high absorption coefficient, high carrier mobility and ideal band gap, they are ideal materials for environmentally friendly perovskite solar cells. However, compared with lead-based perovskite solar cells, the open circuit voltage of tin-based perovskite solar cells is lower, resulting in insufficient light response in the near-infrared region of solar cells prepared from them. One of the main reasons limiting the performance improvement of tin-based perovskites is that the shallow energy level of tin-based perovskites does not match the energy level of traditional fullerene electron transport layers; another important reason is that the current mainstream metal halide perovskite materials can only absorb a small part of ultraviolet (UV) and visible light (400-800nm), accounting for only 45-50% of the entire solar spectrum, thus limiting effective light absorption and photoelectric conversion efficiency. Therefore, designing new electron transport layer materials is to solve the current energy level mismatch problem of tin-based perovskite solar cells, and extending the photoelectric response to the near-infrared region has become an urgent topic in the research of tin-based perovskite solar cells.
[0005] In view of this, the inventors, relying on their many years of experience and practice in related industries, propose a solar cell and a method for preparing the same, as well as a method for improving the light absorption and transmission properties of a tin-based perovskite layer, in order to overcome the defects of the prior art. Summary of the invention
[0006] The purpose of the present invention is to overcome the two technical problems faced by the above-mentioned tin-based perovskite, and to provide a solar cell and a preparation method thereof, and a method for improving the light absorption and transmission characteristics of a tin-based perovskite layer. The present invention uses a tin-based perovskite layer film prepared by a small molecule receptor with light absorption ability and a suitable energy level to significantly improve the light response of the perovskite light absorption layer to the long-wave direction, promote electron migration, inhibit the non-radiative recombination of carriers, and improve the problem of low open-circuit voltage of traditional tin-based perovskite solar cells; in addition, the solar cell prepared based on the above-mentioned tin-based perovskite layer significantly improves the problem of insufficient light response in the near-infrared region of traditional tin-based perovskite solar cells.
[0007] The purpose of the present invention is to be solved by the following technical solutions:
[0008] A method for improving the light absorption and transmission properties of a tin-based perovskite layer, wherein a small molecule receptor is dissolved in a DMF / DMSO solution, and then added to a tin-based perovskite precursor solution based on a comparable solvent, and then annealed and washed to obtain a tin-based perovskite film with a bulk heterojunction structure;
[0009] The molecular structure of the small molecule receptor is as follows:
[0010]
[0011] Wherein, R is a single or multiple groups selected from n-hexyl, hydroxyl, and sulfonic acid groups in any combination.
[0012] Furthermore, the tin-based perovskite film has an ABX3 structure, wherein A is methylamine CH3NH2 or formamidine HC(NH2)2; B is a cation Sn 2+ ; X is an anion Cl - ,Br - and I - Any combination of one or more anions.
[0013] Furthermore, the tin-based perovskite precursor includes tin halide and organic / inorganic salt, the tin halide is BX2; and the organic / inorganic salt is AX.
[0014] Furthermore, the concentration of the DMF / DMSO solution is 5-50 mg / ml; and the annealing temperature is 80-100°C.
[0015] A solar cell comprises a substrate, an anode layer, a hole transport layer, a perovskite light absorption layer, an electron transport layer, a hole blocking layer and a cathode which are stacked in sequence, wherein the perovskite light absorption layer is a tin-based perovskite film prepared by the above method.
[0016] Furthermore, the thickness of the perovskite light-absorbing layer is 200-400 nm.
[0017] Furthermore, the sheet resistance of the anode layer is 10-20Ω, and the thickness is 100-120nm; the thickness of the hole transport layer is 30nm; the thickness of the electron transport layer is 40nm; the thickness of the hole blocking layer is 5nm; and the thickness of the cathode is 100-150nm.
[0018] Furthermore, the substrate is a flexible substrate; wherein the flexible substrate is a polyester or polyphthalimide compound;
[0019] The anode layer is made of inorganic material or organic conductive polymer; wherein, when the anode layer is made of inorganic material, the inorganic material is a metal oxide selected from indium tin oxide, zinc oxide or tin oxide, or a metal selected from gold, copper, silver or zinc; when the anode layer is made of organic conductive polymer, the organic conductive polymer is polythiophene, polyethylene sodium basic benzene sulfonate or polyaniline;
[0020] The hole transport layer is made of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) or nickel oxide or copper thiocyanate;
[0021] The electron transport layer is made of fullerene (C60) or fullerene derivatives (C60PCBM, C70PCBM, ICBA);
[0022] The cathode is made of metal or a fluoride and metal composite electrode; wherein the metal is gold, silver or aluminum; the composite electrode is formed by a composite of lithium fluoride and metal silver, gold or copper.
[0023] A method for preparing the above solar cell comprises the following steps:
[0024] Step 1: Clean the transparent conductive substrate with ethanol, acetone ultrasound and deionized water ultrasound, and place it under an infrared lamp for drying after cleaning. The ITO film on the substrate is used as the anode layer of the device. The substrate is a flexible substrate, and the flexible substrate is a polyester or polyimide compound; the anode layer is made of inorganic materials or organic conductive polymers, and the inorganic material is indium tin oxide or tin fluoride oxide, and the organic conductive polymer is polythiophene, sodium polyvinylbenzene sulfonate or polyaniline;
[0025] Step 2: Use oxygen plasma to treat the substrate dried in step 1, and then spin-coat a hole transport layer on the substrate. Select poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, the mass fraction of PEDOT:PSS solution is 10%, and use a gelator to spin-coat the solution. After drying, a hole transport layer is obtained;
[0026] Step 3: Prepare a tin-based perovskite light-absorbing layer on the hole transport layer prepared in step 2 by a one-step spin coating anti-solvent method, wherein the halide is tin iodide; and the ligand is methylamine iodide or formamidine iodide;
[0027] Step 4: The tin-based perovskite light-absorbing layer prepared in step 3 is used to prepare an electron transport layer by vacuum evaporation, wherein the material of the electron transport layer is fullerene and its derivatives;
[0028] Step 5: vacuum evaporating a hole blocking layer on the electron transport layer prepared in step 4, wherein the hole blocking layer material is o-phenanthroline or o-phenanthroline compounds;
[0029] Step 6: Keep the pressure in the vacuum chamber unchanged, and evaporate a metal or a fluoride and metal composite layer on the hole blocking layer prepared in step 5 as the cathode layer of the device.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention provides a method for improving the light absorption and transmission characteristics of a tin-based perovskite layer, thereby improving the photoelectric conversion efficiency of solar cells. Compared with the traditional tin-based perovskite solar cells with a planar heterojunction structure, the small molecule acceptor and the tin-based perovskite of the present invention together form a tin-based perovskite light absorption layer with a bulk heterojunction structure. The tin-based perovskite layer absorbs high-energy photons, and the small molecule acceptor absorbs low-energy photons, thereby improving the problem of insufficient light response in the near-infrared region of traditional tin-based perovskite solar cells.
[0032] Furthermore, the small molecule receptor of the present invention has chiral groups on both sides, which reduces the symmetry, increases the free volume, and has better solubility in a specific ratio of DMF / DMSO organic solvent; at the same time, the small molecule receptor has a suitable energy level, which acts as a gradient energy level at the interface between the tin-based perovskite light-absorbing layer and the fullerene electron transport layer, can promote electron migration, inhibit non-radiative recombination of carriers, and improve the problem of low open-circuit voltage of traditional tin-based perovskite solar cells.
[0033] Furthermore, the light-absorbing layer of the bulk heterojunction structure is prepared by blending precursor solutions. Compared with the layered tandem structure, the corrosion effect of organic solvents on the lower perovskite film during the spinning of the upper structure is greatly reduced.
[0034] Furthermore, the small molecule receptor is not limited to one or several structures. The combination of substituents on both sides of the molecule and at R2 determines that the small molecule receptor is a material that can be easily modified to improve photoelectric properties. In addition, by setting the use concentration and annealing time of the small molecule receptor, targeted modifications can be made to various types of tin-based perovskites, making it a universal material for improving photoelectric properties.
[0035] 2. The present invention provides a solar cell, comprising a substrate, an anode layer, a hole transport layer, a light absorbing layer, an electron transport layer, a hole blocking layer and a cathode stacked in sequence from bottom to top. The light absorbing layer is a tin-based perovskite film of a certain thickness, which can effectively exert the photoelectric properties of the bulk heterojunction tin-based perovskite film, not only ensuring full absorption of visible light, but also not affecting the electrical transmission properties. In addition, the light absorbing layer of the solar cell device is prepared by using tin element, which is less toxic than the existing lead element, and the divalent tin ions are degraded into eco-friendly tin dioxide when exposed to air, which is almost harmless to the environment.
[0036] 3. The present invention also discloses a method for preparing a solar cell. The preparation process of the solar cell can achieve stable preparation of the device and ensure uniformity and repeatability of efficiency.
[0037] In summary, the present invention makes up for the defect of insufficient light response of the existing tin-based perovskite light-absorbing layer in the near-infrared region, promotes carrier migration at the interface, and solves the problem of corrosion of the cleaned perovskite film by organic solvents. The present invention has been verified in practice, and the conversion efficiency of solar cell devices is increased by more than 20% compared with the existing technology, which can fully meet the needs of commercial use of devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0040] Figure 1 This is a schematic diagram of the structure of a tin-based perovskite solar cell device of the present invention;
[0041] Figure 2 It is a comparison diagram of spectral response test curves of a bulk heterojunction tin-based perovskite solar cell device of an embodiment of the present invention and an existing tin-based perovskite solar cell device under the same conditions;
[0042] Figure 3 A comparison diagram of voltage-current density curves of a bulk heterojunction tin-based perovskite solar cell device of an embodiment of the present invention and an original tin-based perovskite solar cell device under the same conditions;
[0043] Figure 4 is a comparison diagram of ultraviolet-visible light absorption test curves of the bulk heterojunction structure tin-based perovskite solar cell device of Example 2 of the present invention and the original tin-based perovskite solar cell device under the same conditions;
[0044] Figure 5 It is a comparison diagram of the voltage-current density curves of the bulk heterojunction structure tin-based perovskite solar cell device of Example 2 of the present invention and the original tin-based perovskite solar cell device under the same conditions.
[0045] Among them: 1 is the substrate; 2 is the anode layer; 3 is the hole transport layer; 4 is the perovskite layer; 5 is the electron transport layer; 6 is the hole blocking layer; and 7 is the cathode. DETAILED DESCRIPTION
[0046] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of devices consistent with some aspects of the present invention as detailed in the appended claims.
[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0048] The present invention provides a method for improving the light absorption and transmission characteristics of a tin-based perovskite layer. A low-symmetry small molecule acceptor is dissolved in a DMF / DMSO solution, and then added into a tin-based perovskite precursor solution based on a comparable solvent for full mixing. The solution is annealed and washed to obtain a tin-based perovskite film with a bulk heterojunction structure. The low symmetry of the small molecule acceptor is used to increase its solubility in an organic solvent. Meanwhile, the small molecule acceptor has a suitable energy level and light absorption capacity in a long-wave direction, thereby improving the light absorption and transmission characteristics of the tin-based perovskite film.
[0049] Specifically, the molecular structure of the small molecule receptor of the present invention is as follows:
[0050]
[0051] Wherein, R is a single or multiple groups selected from n-hexyl, hydroxyl, and sulfonic acid groups in any combination.
[0052] The tin-based perovskite film of the present invention has an ABX3 structure, wherein A is methylamine CH3NH2 or formamidine HC(NH2)2; B is a cation Sn 2 + ; X is an anion Cl - ,Br - and I - Any combination of one or more anions.
[0053] The present invention dissolves a low-symmetry small molecule receptor in a DMF / DMSO solvent, and then adds the solvent-based tin-based perovskite precursor solution to fully blend the solution, with a concentration of 5 to 50 mg / ml; then anneals the solution at 80 to 100° C.; and finally obtains a tin-based perovskite light-absorbing layer film with a bulk heterojunction structure having improved quality.
[0054] Specifically, the tin-based perovskite precursor includes a tin halide and an organic / inorganic salt, wherein the tin halide is BX2, wherein B is a cation Sn 2+ ; X is an anion Cl - ,Br - and I - Any combination of one or more anions; the organic / inorganic salt is AX, wherein A is methylamine CH3NH2 or formamidine HC(NH2)2; B is a cation Sn 2+ .
[0055] like Figure 1As shown, the present invention provides a solar cell device, which includes, from bottom to top, a stacked substrate 1, an anode layer 2, a hole transport layer 3, a perovskite light absorption layer 4, an electron transport layer 5, a hole blocking layer 6 and a cathode 7; wherein the perovskite light absorption layer 4 is prepared by the above-mentioned method for improving the light absorption and transmission characteristics of the tin-based perovskite layer, that is, a tin-based perovskite light absorption layer, and its thickness is 200 to 400 nm.
[0056] Specifically, the substrate 1 is glass or a flexible substrate, and the flexible substrate is a polyester or polyimide compound.
[0057] The anode layer 2 is made of inorganic material or organic conductive polymer. The inorganic material is a metal oxide of indium tin oxide, zinc oxide or tin oxide or a metal of gold, copper, silver or zinc. The organic conductive polymer is polythiophene, polyethylene sodium benzene sulfonate or polyaniline.
[0058] The material of the hole transport layer 3 includes: poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid), nickel oxide or copper thiocyanate.
[0059] The material of the electron transport layer 5 includes: fullerene (C60) or fullerene derivatives (C60PCBM, C70PCBM, ICBA).
[0060] The material of cathode 7 is metal or a composite electrode of fluoride and metal, and the metal is selected from gold, silver or aluminum; the composite electrode is lithium fluoride and metal silver, gold or copper.
[0061] See also Figure 1 , the preferred structure of the solar cell device of the present invention is as follows:
[0062] From bottom to top, it includes glass (plastic) substrate 1 / ITO (anode layer) 2 / hole transport layer 3 / perovskite light absorption layer 4 / electron transport layer 5 / hole blocking layer 6 / cathode layer 7.
[0063] According to the above structural formula, the detailed implementation method is described as follows in combination with the preparation steps of the device:
[0064] Step 1: Clean the transparent conductive substrate 1 (ITO glass) by using ethanol, acetone ultrasound and deionized water ultrasound, and place it under an infrared lamp for drying after cleaning, wherein the ITO film on the transparent conductive substrate 1 is used as the anode layer 2 of the device, and the square resistance of the ITO film is 10-20Ω, and the film thickness is 100-120nm. In addition to glass, the substrate can also be a flexible substrate, wherein the flexible substrate can be a polyester or polyimide compound. The anode layer 2 can be made of inorganic materials or organic conductive polymers, and the inorganic material can be selected from indium tin oxide (ITO), fluorine tin oxide (FTO), and organic conductive polymers such as polythiophene, sodium polyvinylbenzene sulfonate or polyaniline.
[0065] Step 2, preparation of hole transport layer 3: the dried substrate is treated with oxygen plasma for 15 minutes, and then the hole transport layer is spin-coated on the substrate, preferably poly (3, 4-ethylenedioxythiophene) - polystyrene sulfonic acid (PEDOT:PSS for short), the mass fraction of PEDOT:PSS solution is 10%, and the solution is spin-coated with a coating machine, the rotation speed is selected at 1500rpm, the coating time is 60s, the drying temperature of the obtained hole transport layer film is 150°C, the drying time is 0.5 hours, and the film thickness is 30nm.
[0066] Step 3: Preparation of perovskite light absorbing layer 4: Prepare a perovskite light absorbing layer 4 with a bulk heterojunction structure on the hole transport layer 3, and use a one-step spin coating anti-solvent method to prepare the perovskite light absorbing layer. Among them, the halide is tin iodide (SnI2); the ligand is methylamine iodide (abbreviated as CH3NH3I) and formamidine iodide (abbreviated as (NH2)2CHI).
[0067] Step 4: Preparation of electron transport layer 5: The prepared perovskite layer 4 is used to prepare electron transport layer 5 by vacuum evaporation. The electron transport material is fullerene and its derivatives, preferably fullerene (abbreviated as C60). The heating temperature is 600°C, the evaporation rate is 0.1nm / s, and the thickness is 40nm.
[0068] Step 5, preparation of hole blocking layer 6: vacuum evaporation of hole blocking layer 6 is performed on the prepared electron transport layer 5. The hole blocking layer material is o-phenanthroline and o-phenanthroline compounds, preferably 2,9-dimethyl-4,7-biphenyl-1,10-o-phenanthroline (BCP for short), the evaporation rate of the material film is 0.01-0.2 nm / s, and the film thickness is 5 nm.
[0069] Step 6, preparation of cathode 7: Keep the pressure in the vacuum chamber unchanged, and deposit metal or a composite layer of fluoride and metal on the hole blocking layer 6 as the cathode layer of the device, with a film thickness of 100-150 nm. The metal is selected from gold, silver or copper, preferably silver.
[0070] In order to further verify the effect of preparing solar cells by the method of the present invention, the following specific examples were carried out:
[0071] Example 1
[0072] like Figure 1 As shown, the structure of the solar cell device prepared by the present invention is from bottom to top: glass substrate / ITO (100nm) / PEDOT:PSS (30nm) / BHJHC (NH2) 2SnI3 (400nm) / C60 (40n m) / BCP (5nm) / Ag (120nm).
[0073] The preparation method is as follows:
[0074] S1. Cleaning of the glass substrate pre-engraved with ITO: Clean the transparent conductive substrate 1 (ITO glass) by using ethanol, acetone ultrasound and deionized water ultrasound, and place it under an infrared lamp for drying after cleaning, wherein the ITO film on the transparent conductive substrate 1 is used as the anode layer 2 of the device, and the square resistance of the ITO film is 10-20Ω, and the film thickness is 100-120nm;
[0075] S2. Preparation of hole transport layer: The dried substrate was treated with oxygen plasma for 15 minutes, and then placed on a KW-4A coating machine. The prepared PEDOT:PSS solution was spin-coated into a film using a static batching method. The speed of the coating machine was 1500 rpm, and the coating time was controlled at 60 s. The sample was dried at 150°C for 0.5 hours, and the thickness was 30 nm.
[0076] S3, preparation of perovskite layer: weigh 372 mg of SnI2, 172 mg of (formamidine iodide) FAI, add the above materials to 1.0 mL of DMSO mixed solution to form a precursor solution and heat and stir at 60 ° C overnight. After filtration, spin coat it on the hole transport layer at a speed of 5000 rpm, and the spin coating time is 60 s; and at the 10th second, 0.7 mL of chlorobenzene is added to the top of the solution. After spin coating, the substrate is annealed on a 100 ° C drying table for 10 minutes, and the film thickness is 400 nm. For the bulk heterojunction structure film formed by the blending of tin-based perovskite and small molecule receptors, the low-symmetry small molecule receptor is dissolved in DMF / DMSO solvent, and then added to the tin-based perovskite precursor solution based on the same solvent to fully blend, and the concentration is selected from 5 to 50 mg / ml. Figure 2 This is a comparison of the spectral response test curves of a bulk heterojunction tin-based perovskite solar cell device and an original tin-based perovskite solar cell device under the same conditions. It can be seen that the external quantum efficiency of the bulk heterojunction device is significantly increased.
[0077] S4, preparation of electron transport layer 5: The prepared perovskite layer 4 is used to prepare electron transport layer 5 by vacuum evaporation. The electron transport material is fullerene and its derivatives, preferably fullerene (abbreviated as C60). The heating temperature is 600°C, the evaporation rate is 0.1nm / s, and the thickness is 40nm.
[0078] S5, preparation of hole blocking layer 6: vacuum evaporation of hole blocking layer 6 is performed on the prepared electron transport layer 5. The hole blocking layer material is o-phenanthroline and o-phenanthroline compounds, preferably 2,9-dimethyl-4,7-biphenyl-1,10-o-phenanthroline (BCP for short), the evaporation rate of the material film is 0.1 nm / s, and the film thickness is 5 nm.
[0079] S6, preparation of cathode 7: keeping the pressure in the vacuum chamber unchanged, evaporating metal on the hole blocking layer 6 as the cathode layer of the device, with a film thickness of 120 nm. Silver is selected as the metal.
[0080] After testing the solar cells prepared above, the results are as follows Figure 3 As shown, Figure 3 This is a comparison diagram of the voltage-current density curves of a bulk heterojunction tin-based perovskite solar cell device and an original tin-based perovskite solar cell device under the same conditions. The device performance has been greatly improved; its open circuit voltage has increased from 0.52V to 0.58V, and the energy conversion efficiency has increased from 6.9% to 9.1%. That is, this method has significantly improved the problem of low open circuit voltage of traditional tin-based perovskite solar cells.
[0081] Example 2
[0082] like Figure 1 As shown, the structure of the solar cell device prepared by the present invention is from bottom to top: glass substrate / ITO (100nm) / PEDOT:PSS (30nm) / BHJHC (NH2) 2SnI3 (350nm) / C60 (50nm) / BCP (5nm) / Ag (150nm).
[0083] The preparation method is as follows:
[0084] S1. Cleaning of the glass substrate pre-engraved with ITO: Clean the transparent conductive substrate 1 (ITO glass) by using ethanol, acetone ultrasound and deionized water ultrasound, and place it under an infrared lamp for drying after cleaning, wherein the ITO film on the transparent conductive substrate 1 is used as the anode layer 2 of the device, and the square resistance of the ITO film is 10-20Ω, and the film thickness is 100-120nm;
[0085] S2. Preparation of hole transport layer: The dried substrate was treated with oxygen plasma for 15 minutes, and then placed on a KW-4A coating machine. The prepared PEDOT:PSS solution was spin-coated into a film using a static batching method. The speed of the coating machine was 1500 rpm, and the coating time was controlled at 60 s. The sample was dried at 150°C for 0.5 hours, and the thickness was 30 nm.
[0086] S3, preparation of perovskite layer: weigh 372 mg of SnI2, 172 mg of (formamidine iodide) FAI, add the above materials to 1.0 mL of DMSO mixed solution to form a precursor solution and heat and stir at 60 ° C overnight. After filtration, spin coat it on the hole transport layer at a speed of 6000 rpm, and the spin coating time is 60 s; and at the 10th second, 0.7 mL of chlorobenzene is added to the top of the solution. After spin coating, the substrate is annealed on a 100 ° C drying table for 10 minutes, and the film thickness is 350 nm. For the bulk heterojunction structure film formed by the blending of tin-based perovskite and small molecule receptors, the low-symmetry small molecule receptor is dissolved in DMF / DMSO solvent, and then added to the tin-based perovskite precursor solution based on the same solvent to fully blend, and the concentration is selected from 5 to 50 mg / ml. Figure 4 This is the UV-visible light absorption test curve of the bulk heterojunction structure tin-based perovskite solar cell device and the original tin-based perovskite solar cell device under the same conditions. It can be seen that the light absorption capacity of the bulk heterojunction structure device is significantly increased.
[0087] S4, preparation of electron transport layer 5: The prepared perovskite layer 4 is subjected to vacuum evaporation to prepare electron transport layer 5. The electron transport material is fullerene and its derivatives, preferably fullerene (referred to as C60). The heating temperature is 600°C, the evaporation rate is 0.1nm / s, and the thickness is 50nm.
[0088] S5, preparation of hole blocking layer 6: vacuum evaporation of hole blocking layer 6 is performed on the prepared electron transport layer 5. The hole blocking layer material is o-phenanthroline and o-phenanthroline compounds, preferably 2,9-dimethyl-4,7-biphenyl-1,10-o-phenanthroline (BCP for short), the evaporation rate of the material film is 0.1 nm / s, and the film thickness is 5 nm.
[0089] S6, preparation of cathode 7: keeping the pressure in the vacuum chamber unchanged, evaporating metal on the hole blocking layer 6 as the cathode layer of the device, with a film thickness of 150 nm. Silver is selected as the metal.
[0090] After testing the solar cells prepared above, the results are as follows Figure 5 As shown, Figure 5 This is a comparison diagram of the voltage-current density curves of a bulk heterojunction tin-based perovskite solar cell device and an original tin-based perovskite solar cell device under the same conditions. The device performance has been greatly improved; its open circuit voltage has increased from 0.55V to 0.58V, and the energy conversion efficiency has increased from 7.3% to 9.2%. That is, this method has significantly improved the problem of low open circuit voltage of traditional tin-based perovskite solar cells.
[0091] Example 3
[0092] like Figure 1As shown, the structure of the solar cell device prepared by the present invention is from bottom to top: glass substrate / ITO (100nm) / PEDOT:PSS (30nm) / BHJCH3NH3SnI3 (300nm) / C60 (50nm) / BCP (5nm) / Ag (150nm).
[0093] The preparation method is as follows:
[0094] S1. Cleaning of the glass substrate pre-engraved with ITO: Clean the transparent conductive substrate 1 (ITO glass) by using ethanol, acetone ultrasound and deionized water ultrasound, and place it under an infrared lamp for drying after cleaning, wherein the ITO film on the transparent conductive substrate 1 is used as the anode layer 2 of the device, and the square resistance of the ITO film is 10-20Ω, and the film thickness is 100-120nm;
[0095] S2. Preparation of hole transport layer: The dried substrate was treated with oxygen plasma for 15 minutes, and then placed on a KW-4A coating machine. The prepared PEDOT:PSS solution was spin-coated into a film using a static batching method. The speed of the coating machine was 1500 rpm, and the coating time was controlled at 60 s. The sample was dried at 150°C for 0.5 hours, and the thickness was 30 nm.
[0096] S3, preparation of perovskite layer: weigh 372 mg of SnI2, 159 mg of (methylamine iodide) MAI, add the above materials to 1.0 mL of DMSO mixed solution to form a precursor solution and heat and stir at 60 ° C overnight. After filtration, spin coat it on the hole transport layer at a speed of 6000 rpm, and the spin coating time is 60 s; and at the 10th second, 0.7 mL of chlorobenzene is added to the top of the solution. After spin coating, the substrate is annealed on a 100 ° C drying table for 10 minutes, and the film thickness is 300 nm. For the bulk heterojunction structure film formed by the blending of tin-based perovskite and small molecule receptors, the low-symmetry small molecule receptor is dissolved in DMF / DMSO solvent, and then added to the tin-based perovskite precursor solution based on the same solvent to fully blend, and the concentration is selected from 5 to 50 mg / ml.
[0097] S4, preparation of electron transport layer 5: The prepared perovskite layer 4 is subjected to vacuum evaporation to prepare electron transport layer 5. The electron transport material is fullerene and its derivatives, preferably fullerene (referred to as C60). The heating temperature is 600°C, the evaporation rate is 0.1nm / s, and the thickness is 50nm.
[0098] S5, preparation of hole blocking layer 6: vacuum evaporation of hole blocking layer 6 is performed on the prepared electron transport layer 5. The hole blocking layer material is o-phenanthroline and o-phenanthroline compounds, preferably 2,9-dimethyl-4,7-biphenyl-1,10-o-phenanthroline (BCP for short), the evaporation rate of the material film is 0.1 nm / s, and the film thickness is 5 nm.
[0099] S6, preparation of cathode 7: keeping the pressure in the vacuum chamber unchanged, evaporating metal on the hole blocking layer 6 as the cathode layer of the device, with a film thickness of 150 nm. Silver is selected as the metal.
[0100] The performance of devices prepared from the treated perovskite layer has been greatly improved: the open circuit voltage has increased from 0.49V to 0.56V, and the energy conversion efficiency has increased from 5.93% to 7.3%.
[0101] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.
[0102] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A method for improving the light absorption and transmission properties of a tin-based perovskite layer, characterized in that: The small molecule receptor is dissolved in a DMF / DMSO solution, and then added into a tin-based perovskite precursor solution based on a similar solvent, and then annealed and washed to obtain a tin-based perovskite film with a bulk heterojunction structure; The molecular structure of the small molecule receptor is as follows: Wherein, R is a single or multiple groups selected from n-hexyl, hydroxyl, and sulfonic acid groups in any combination.
2. The method for improving the light absorption and transmission characteristics of a tin-based perovskite layer according to claim 1, characterized in that: The tin-based perovskite film has an ABX3 structure, wherein A is methylamine CH3NH2 or formamidine HC(NH2)2; B is a cation Sn 2+ ; X is an anion Cl - ,Br - and I - Any combination of one or more anions.
3. A method for improving the light absorption and transmission characteristics of a tin-based perovskite layer according to claim 2, characterized in that: The tin-based perovskite precursor includes tin halide and organic / inorganic salt, the tin halide is BX2; the organic / inorganic salt is AX.
4. The method for improving the light absorption and transmission characteristics of a tin-based perovskite layer according to claim 1, characterized in that: The concentration of the DMF / DMSO solution is 5-50 mg / ml; the annealing temperature is 80-100°C.
5. A solar cell, characterized in that: The invention comprises a substrate (1), an anode layer (2), a hole transport layer (3), a perovskite light absorbing layer (4), an electron transport layer (5), a hole blocking layer (6) and a cathode (7) which are stacked in sequence from bottom to top, wherein the perovskite light absorbing layer (4) is a tin-based perovskite film prepared by the method according to any one of claims 1 to 4.
6. A solar cell according to claim 5, characterized in that: The thickness of the perovskite light-absorbing layer (4) is 200-400 nm.
7. A solar cell according to claim 5, characterized in that: The anode layer (2) has a square resistance of 10-20Ω and a thickness of 100-120nm; the hole transport layer (3) has a thickness of 30nm; the electron transport layer (5) has a thickness of 40nm; the hole blocking layer (6) has a thickness of 5nm; and the cathode (7) has a thickness of 100-150nm.
8. A solar cell according to claim 5, characterized in that: The substrate (1) is a flexible substrate; wherein the flexible substrate is a polyester or polyphthalimide compound; The anode layer (2) is made of inorganic material or organic conductive polymer; wherein, when the anode layer (2) is made of inorganic material, the inorganic material is a metal oxide selected from indium tin oxide, zinc oxide or tin oxide, or a metal selected from gold, copper, silver or zinc; when the anode layer (2) is made of organic conductive polymer, the organic conductive polymer is polythiophene, polyethylene sodium benzene sulfonate or polyaniline; The hole transport layer (3) is made of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) or nickel oxide or copper thiocyanate; The electron transport layer (5) is made of fullerene or a fullerene derivative; The cathode (7) is made of metal or a fluoride and metal composite electrode; wherein the metal is gold, silver or aluminum; and the composite electrode is formed by a composite of lithium fluoride and metal silver, gold or copper.
9. A method for preparing the solar cell according to any one of claims 5 to 8, characterized in that: The following steps are involved: Step 1: Clean the transparent conductive substrate with ethanol, acetone ultrasound and deionized water ultrasound, and place it under an infrared lamp for drying after cleaning. The ITO film on the substrate is used as the anode layer of the device. The substrate is a flexible substrate, and the flexible substrate is a polyester or polyimide compound; the anode layer is made of inorganic materials or organic conductive polymers, and the inorganic material is indium tin oxide or tin fluoride oxide, and the organic conductive polymer is polythiophene, sodium polyvinylbenzene sulfonate or polyaniline; Step 2: Use oxygen plasma to treat the substrate dried in step 1, and then spin-coat a hole transport layer on the substrate. Select poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid, the mass fraction of PEDOT:PSS solution is 10%, and use a gelator to spin-coat the solution. After drying, a hole transport layer is obtained; Step 3: Prepare a tin-based perovskite light-absorbing layer on the hole transport layer prepared in step 2 by a one-step spin coating anti-solvent method, wherein the halide is tin iodide; and the ligand is methylamine iodide or formamidine iodide; Step 4: The tin-based perovskite light-absorbing layer prepared in step 3 is used to prepare an electron transport layer by vacuum evaporation, wherein the material of the electron transport layer is fullerene and its derivatives; Step 5: vacuum evaporating a hole blocking layer on the electron transport layer prepared in step 4, wherein the hole blocking layer material is o-phenanthroline or o-phenanthroline compounds; Step 6: Keep the pressure in the vacuum chamber unchanged, and evaporate a metal or a fluoride and metal composite layer on the hole blocking layer prepared in step 5 as the cathode layer of the device.
Citation Information
Patent Citations
Method for improving growth quality of perovskite crystal and solar cell device
CN105870341A
Solar cell and preparation method thereof and method for improving transmission characteristic of perovskite layer
CN109411607A